2011
DOI: 10.3844/ajassp.2011.201.205
|View full text |Cite
|
Sign up to set email alerts
|

The Phytochemical Contents and Antimicrobial Activities of Malaysian <i>Calophyllum Rubiginosum</i>

Abstract: Problem statement: Many species of plants in Malaysia are widely used in folk medicine. However, Calophyllum species have been used in traditional medicine for their therapeutic values for many years. Several studies reported that antimicrobial, antifungal, anti-HIV and anti-cancer compounds were isolated from numerous Calophyllum species. Approach: The stem bark was extracted by EtOH, after with it was fractionated with n-Hexane, Dichloromethane (DCM) and MeOH by using vacuum liquid chromatography apparatus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
(17 reference statements)
6
9
1
Order By: Relevance
“…Out of these 203 milk samples, a total of 148 different bacterial isolates were recovered, they were identified by biochemical test and found the isolated bacteria belonging to eight species as in Table-2 and Figure-2. These results were in agreement with many authors [38,39]. They are considered the culturing of bacterial is a gold standard method.…”
Section: Discussionsupporting
confidence: 93%
“…Out of these 203 milk samples, a total of 148 different bacterial isolates were recovered, they were identified by biochemical test and found the isolated bacteria belonging to eight species as in Table-2 and Figure-2. These results were in agreement with many authors [38,39]. They are considered the culturing of bacterial is a gold standard method.…”
Section: Discussionsupporting
confidence: 93%
“…They found that the methanol extract was the most effective. Our results also agreed with a previous study (Al-Judaibi and Al-Yousef, 2013) Screenings of the antimicrobial activity of extracts from plants, honey and black cumin oil were conducted in other studies, which showed that diethyl ether extracts were the most effective antimicrobial compounds and their activity was the most pronounced against grampositive bacteria (Nostro et al, 2000;Adam, 2013 (Dorman and Deans, 2000;ALkhamaiseh et al, 2011;Kamaraj et al, 2012;Akhila et al, 2013;Choudhury et al, 2013;Hasan et al, 2013b;Sureshjani et al, 2013;Mohammadi-Sichani et al, 2013;Ndjateu et al, 2014).…”
Section: Disscusionsupporting
confidence: 81%
“…A total of 132 different bacterial isolates were isolated from 287 cow's milk samples; they were identified by biochemical tests and found to belong to seven different species, as shown in Table 2. Das et al (2010) andAlkhamaiseh et al (2011) believe that bacterial culture is a good standard method for isolating causative bacteria.…”
Section: Discussionmentioning
confidence: 99%